Size optimization of a biomass-fired cogeneration plant CHP/CCHP (Combined heat and power/Combined heat, cooling and power) based on Organic Rankine Cycle for a district network in Spain. (August 2015) - Uris, María; Linares, José Ignacio; Arenas, Eva
Abstract: This paper presents a methodology to optimize the size (electric power) of a cogeneration plant based on a biomass-fired Organic Rankine Cycle and connected to an existing district heating network, maximizing profitability. First, a model to determine the hourly thermal energy demand profile of a location in Spain has been derived, from open access meteorological data included in Spanish building regulations. Partial load model of an organic Rankine plant has also been obtained to increase the operation hours. These tools have been applied to two locations in Spain with different climatic severities, calculating the optimal size of the plant. The business model does not include subsidies. Calculations show that for population between 10, 000 and 20, 000 inhabitants the size of the plant ranges from 2 to 9 MWe and the internal rate of return ranges from 6% to 18%. The coverage of the thermal energy demand ranges from 40% to 80%. Regarding the trigeneration mode, it is concluded that cooling is only worth in locations with high summer severity and in full load operation mode, being the optimal size of the plant smaller in trigeneration mode than in cogeneration. Highlights: Biomass-fired ORC cogeneration plant for district heating/cooling has been assessed. A method to calculate the hourly thermal load has been developed for Spain. CHP vs. CCHP, Off-design operation, population and climate has been analyzed. Profitability is achieved for medium-size villages with plants between 2 and 9 MWe. Trigeneration is only worth with high summer severity and full load operation.